2010
DOI: 10.1111/j.1540-6237.2010.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Constituent Engagement*

Abstract: Objectives. This article updates and expands the research on sex differences in legislators' relationships with constituents. Methods. A 2008 survey of legislators from 26 states is used to collect data on constituent-initiated contact, hours legislators spend keeping in touch with constituents or conducting casework, legislators' use of constituent information, and accuracy of legislators' perceptions of constituents. Results. The findings suggest that female legislators do not differ from male legislators in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Because state legislators come from a wide array of institutional and electoral systems and have diverse demographic traits, they offer an opportunity to explore effects of phenomena not found at the national level in the United States. Research on state legislators has advanced our understanding of the roles of sexual orientation, gender, and race in political phenomena (see, for example, Barrett 1995; Hedge, Button, and Spears 1996; Herrick 2010; Thomas 1992; Thomas and Welch 1991); how institutional features affect aspects of policy making (see, for example, Carey et al 2006; Francis 1985); and factors affecting how legislators make decisions (Hedlund and Freeman 1981; Mooney 1991a; 1991b) and represent their constituents (see, for example, Ellickson and Whistler 2001; Erikson, Luttbeg, and Holloway 1975; Freeman and Richardson 1996; Maestas 2003; Uslaner and Weber 1979). However, the most common method of surveying, mail surveys, is expensive, slow, and has declining response rates.…”
mentioning
confidence: 99%
“…Because state legislators come from a wide array of institutional and electoral systems and have diverse demographic traits, they offer an opportunity to explore effects of phenomena not found at the national level in the United States. Research on state legislators has advanced our understanding of the roles of sexual orientation, gender, and race in political phenomena (see, for example, Barrett 1995; Hedge, Button, and Spears 1996; Herrick 2010; Thomas 1992; Thomas and Welch 1991); how institutional features affect aspects of policy making (see, for example, Carey et al 2006; Francis 1985); and factors affecting how legislators make decisions (Hedlund and Freeman 1981; Mooney 1991a; 1991b) and represent their constituents (see, for example, Ellickson and Whistler 2001; Erikson, Luttbeg, and Holloway 1975; Freeman and Richardson 1996; Maestas 2003; Uslaner and Weber 1979). However, the most common method of surveying, mail surveys, is expensive, slow, and has declining response rates.…”
mentioning
confidence: 99%
“…6. In previous research on constituent-representative relations, women reported receiving more constituent contacts than men (e.g., Herrick 2010;Lazarus and Steigerwalt 2019;Norris 1997;Richardson and Freeman 1995). This scholarship has not, however, been able to account for the horizontal and vertical gender segregation in politics.…”
Section: Discussionmentioning
confidence: 86%
“…Based on previous research, including the increased risk of violence connected with visibility for women politicians, I expect that women will be particularly prone to withdraw from visibility as a result of violence. Regarding distancing from constituents, women representatives seem to prioritize constituency contacts more than men (Herrick 2010; Thomas 1992). This might indicate that they are less prone to decrease their constituent interactions due to violence.…”
Section: Specifying the Gendered Representational Costs Of Violence A...mentioning
confidence: 99%